Development and Validation of the “Physical Functional Impact Index on Chronic Pain” (PFIICP): A Formative Model Approach - Filipe Antunes; Nuno Sousa; Pedro Teixeira (Acta Médica Portuguesa)
Introduction: The development and validation of reliable and valid instruments to assess chronic pain and its impact on daily functioning are crucial in both clinical and research settings. The aim of this study was to develop and validate the scale ‘Physical Function Impact Index on Chronic Pain’ – PFIICP, a novel 12-item questionnaire designed to evaluate the physical functional impact of chronic pain. Methods: A formative measurement model was used. In comparison with other established scales that have emotional, cognitive and social considerations, PFIICP is designed to be more objective, as it focuses only on the relationship between physical performance and the subject’s pain. Results: Data were collected from n = 285 patients at baseline and n = 58 patients at follow-up (3 - 6 months later). Spearman’s rho correlations between the 12 items ranged from 0.153 to 0.793, all statistically significant (p < 0.05), indicating that each item contributes uniquely to the construct. The intraclass correlation coefficient (ICC) for test-retest reliability was 0.788 (95% CI: 0.731 - 0.833), demonstrating good stability over time. Convergent validity was supported by strong Pearson correlations with established measures, including the Brief Pain Inventory (BPI; r = 0.739, p < 0.05) and the Pain Disability Index (PDI; r = 0.739, p < 0.05). Conclusion: These findings suggest that the PFIICP is a robust tool for assessing the functional impact of chronic pain through a formative model approach.